2003
DOI: 10.17660/actahortic.2003.597.30
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of the Essential Oils of Some Spice Herbs

Abstract: Essential oils were obtained from fennel seeds, dill, cumin and coriander. Their antimicrobial activity was tested on isolated clinical specimens of patients treated at the University Hospital of the School of Medicine of Botucatu, SP, UNESP. Microorganisms were grown in BHI (Brain Heart Infusion/Oxoid) at 37 o C/18 hours and resuspended in 0,5 Mac Farland's Standard (1,5 x 10 8 CFU/mL). The diffusion method was performed, putting 10 µl of the essential oils on paper disks (6mm of diameter) (Blank Disks /CECON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…cerevisiae and Candida rugosa among fungi. Stefanini et al [ 87 ] analyzed the antimicrobial activities of EOs of spices (fennel seeds, dill, cumin, and coriander) by determining the DIZs. The results indicated that cumin was effective against E .…”
Section: Cuminmentioning
confidence: 99%
See 1 more Smart Citation
“…cerevisiae and Candida rugosa among fungi. Stefanini et al [ 87 ] analyzed the antimicrobial activities of EOs of spices (fennel seeds, dill, cumin, and coriander) by determining the DIZs. The results indicated that cumin was effective against E .…”
Section: Cuminmentioning
confidence: 99%
“…The antimicrobial activities of four spice EOs against isolated clinical specimens were compared using the diffusion method [ 87 ], and the results showed that coriander oil was active only against Salmonella sp. Dimic et al [ 132 ] tested the antifungal activities of lemon EO, coriander extract and cinnamon extract against five molds ( A. parasiticus , Cladosporium cladosporioides ( C. cladosporioides ), Eurotium herbariorum , Penicillium chrysogenum , and Aspergillus carbonarius ) by the agar dilution method and vapor phase method.…”
Section: Coriandermentioning
confidence: 99%
“…In addition, CEO contains linalool, eugenol, and other phenolic compounds that are known to be either bactericidal or bacteriostatic agents. These components can attack on the phospholipid in cell membrane, causing the increase in permeability and the leakage of cytoplasm, or interact with enzymes located on the cell wall to extend the shelf-life of sausage in CEO samples (Kim, Kim, & Ahn, 2013;Phanthong, Lomarat, Chomnawang, & Bunyapraphatsara, 2013;Stefanini, Figueiredo, Ming, & Junior, 2004).…”
Section: The Microbial Analysismentioning
confidence: 99%
“…Cumin is known for its carminative, stimulant, diuretic, emmanogogic, antispasmodic and astringent properties. The aqueous extract of cumin is reported to inhibit the growth of many pathogens including Escherichia coli, Staphylococcus aureus 8 , Salmonella species 9 , Bacillus cereus and Aspergillus niger 10 . Composition, concentration of the constituents and extraction procedure are some factors which affect the efficiency of the extract.…”
Section: Introductionmentioning
confidence: 99%